KORELASI ANTARA MOTIVASI KERJA DENGAN PELAYANAN PEGAWAI (Studi Pada Kantor Camat Tering Kabupaten Kutai Barat) - Nurningsih, Yunita (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the working motivation has a positive effect on the Quality of Service Employees at Head Office Tering West Kutai.The results showed that there is a positive and significant relationship between the variables of work motivation variable Services Quality Employees at Head Office Tering West Kutai. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.613, which means there is a strong relationship between the two variables.While the results of the t test (t-test) showed that t-empirical generated is equal to 2.653. These results are compared with the prices of the table critical t for n - 2 is 1.690. This means that there is a significant influence between the variables of work motivation on the Quality of Service Employees. Thus it can be said that the goal of this research can be achieved, the problems can be solved and the hypothesis can be proven.